Effects of low-volume functional and running high-intensity interval training on physical fitness in young adults with overweight/obesity - Cao, Meng; Yang, Baiquan; Tang, Yucheng; Wang, Chun; Yin, Lijun (Frontiers in Physiology, 2024)
Objectives: This study examined and compared the effects of functional and running high-intensity interval training (HIIT) on body composition, cardiorespiratory fitness, and muscular fitness of young adults with overweight or obesity. Methods: Forty-five participants (22.1 ± 2.1 years, BMI = 25.2 ± 1.0 kg/m 2 ) were assigned to functional HIIT (HIIT-F; n = 15), running HIIT (HIIT-R; n = 15), or non-training control group (CON; n = 15). Participants in HIIT-F and HIIT-R performed functional exercise based-HIIT (four sets of all-out whole-body exercises including jumping jacks, squats, twist jumps and mountain climbers, et al.) and running HIIT (four sets of running on a treadmill) for 12 weeks, respectively. Body composition, muscular fitness, and cardiorespiratory fitness were assessed pre and post intervention. Results: Both HIIT-F and HIIT-R significantly improved the body composition and cardiorespiratory fitness, with HIIT-F induced greater improvements in lean mass (+1.623 vs. -1.034 kg, P＜0.001), back strength (+6.007 vs. +3.333 kg, P＜0.01), and push-ups (+5.692 vs. 1.923 reps, P＜0.001) than that in HIIT-R. HIIT-R reduced more visceral fat area (VFA) (-11.416 vs. -4.338 cm 2 , P=0.052) and induced similar improvement in cardiorespiratory fitness (VO2max, +2.192 vs. +2.885 mL/kg/min, P=0.792) with HIIT-F. Conclusions: Twelve weeks of HIIT-R or HIIT-F improved physical fitness among young adults with overweight or obesity. Despite the similar impact on cardiorespiratory fitness, HIIT-F generates a better positive effect on muscular fitness relative to HIIT-R, which could be partly explained by the greater increase in lean mass after HIIT-F intervention.